Sytuacje społeczne w szkole dzieci z dysleksją - Rudzińska-Rogoża, Aneta
The subject of the mater is the social situation of children with dyslexia that they meet at school. In the theoretical part of the thesis the subject of dyslexia has been discussed, its influence on a child's development, issue of social situation of a human including the specific social situation of the child at school. The basic contexts indicating those situations have been taken into consideration. That is school (including school grade) but also the family as place of social experiences of the child.
Keywords: pedagogika specjalna; dziecko; pedagogika; szkoła; dysleksja